2018
DOI: 10.5115/acb.2018.51.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces cell death in cervical cancer by reducing O-GlcNAcylation of adenosine monophosphate-activated protein kinase

Abstract: Hyper-O-GlcNAcylation is a general feature of cancer which contributes to various cancer phenotypes, including cell proliferation and cell growth. Quercetin, a naturally occurring dietary flavonoid, has been reported to reduce the proliferation and growth of cancer. Several reports of the anticancer effect of quercetin have been published, but there is no study regarding its effect on O-GlcNAcylation. The aim of this study was to investigate the anticancer effect of quercetin on HeLa cells and compare this wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…[153][154][155][156][157][158][159][160][161] Quercetin exerts anticancer effects in cervical cancer cells by regulating their dysregulated behaviors in proliferation, cell cycle progression, survival, apoptosis, migration, and invasion. 135,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] Isorhamnetin suppresses the proliferation of cervical cancer cells by inducing cell cycle arrest in the G2/M phase. 175 Cordycepin stimulates apoptotic cell death and interferes with the cell cycle through the generation of reactive oxygen species and the repression of cell cycle regulators in cervical cancer cells, 176,177 and sensitizes cervical cancer cells to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[153][154][155][156][157][158][159][160][161] Quercetin exerts anticancer effects in cervical cancer cells by regulating their dysregulated behaviors in proliferation, cell cycle progression, survival, apoptosis, migration, and invasion. 135,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] Isorhamnetin suppresses the proliferation of cervical cancer cells by inducing cell cycle arrest in the G2/M phase. 175 Cordycepin stimulates apoptotic cell death and interferes with the cell cycle through the generation of reactive oxygen species and the repression of cell cycle regulators in cervical cancer cells, 176,177 and sensitizes cervical cancer cells to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to numerous studies, Luteolin is known for it potent prevention and inhibition against cervical cancer [26]. Quercetin decreased cervical cancer cell proliferation and induced cell death [27]. It is showed that caffeic acid isolated from several kinds of vegetables and herbals had anti-proliferative effects on cervical cancer cell lines, this compound can significantly reduce the proliferation of HeLa cells in a time-dependent manner [28].…”
Section: Resultsmentioning
confidence: 99%
“…A yellow water soluble tetrazolium dye thiazolyl blue tetrazolium bromide (MTT; Biosesang, Seongnam, Korea) was used to measure cell viability as described previously [2728]. After removing the culture medium, cells were incubated at 37℃ with 5 mg/ml MTT in PBS for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%